STUDY OF THE LEVEL OF KNOWLEDGE ABOUT HAND DISINFECTION AND THE APPLICATION OF ROUTINE DISINFECTION MEASURES AMONG DENTAL TECHNICIANS - Velina Stoeva; Meri Hristamyan; Aleksandar Atanasovski (Peytchinski Publishing, 2024)
Purpose: To study the level of knowledge about hand disinfection and the application of routine disinfection measures in everyday practice among dental technician students from the Medical College of Plovdiv and practicing dental technicians. Material and methods: For the period September 2019 - January 2020, an anonymous 19-question survey was conducted among a total of 92 dental technicians. All statistical analyses were performed with SPSS version 24. A p-value below 0.05 was considered statistically significant. Results: Of the respondents, 34.8% (n = 30) were students, and 65.2% (n = 62) were practicing dental technicians. The majority (77.2% (n = 71)) rate the hands as a factor for the transmission of microorganisms from person to person, but for 16.3% (n = 15), the hands pose a risk only if they are visibly contaminated. Only 31.5% (n = 29) disinfect their hands for the recomended 30 seconds. When working with dental impressions and dentures, 59.8% (n = 55) know that they must always be disinfected before working with them. The most commonly used preparations for disinfection of impressions are alcohols in 44.6% (n = 41), but 22.8% (n = 21) wrongly only use water and soap. Only 1/3 correctly state that the finished dentures should be disinfected before being handed to the dentist. Conclusion: Effective communication and coordination between the dental laboratory technicians and the dental office staff are critical components of a successful infection control program related to dental care.